1
$\begingroup$

I am a little rusty with initial conditions. If anyone can confirm that I nailed this then I would be very happy. i need to write about five terms in my series to the solution of

$xy'' + y = 0$

$y(1) = 5$

$y'(1) = 0$

So my solution will look something like $y = \sum_{n=0}^{\infty}a_n (x - 1)^n$

$y' = \sum_{n=1}^{\infty}na_n (x - 1)^{n-1}$

$y'' = \sum_{n=2}^{\infty}n(n-1)a_n (x - 1)^{n-2}$

$\begin{align}xy'' + y & = x\sum_{n=2}^{\infty}n(n-1)a_n (x - 1)^{n-2} + \sum_{n=0}^{\infty}a_n (x - 1)^n \\ & = (x - 1 + 1) \sum_{n=2}^{\infty}n(n-1)a_n (x - 1)^{n-2} + \sum_{n=0}^{\infty}a_n (x - 1)^n \\ & = \sum_{n=2}^{\infty}n(n-1)a_n (x - 1)^{n-1} + \sum_{n=2}^{\infty}n(n-1)a_n (x - 1)^{n-2} + \sum_{n=0}^{\infty}a_n (x - 1)^n \\ & = \sum_{n=1}^{\infty}n(n+1)a_{n+1} (x - 1)^n + \sum_{n=0}^{\infty}(n+2)(n+1)a_{n+2} (x - 1)^n + \sum_{n=0}^{\infty}a_n (x - 1)^n \\ & = \sum_{n=0}^{\infty}n(n+1)a_{n+1} (x - 1)^n + \sum_{n=0}^{\infty}(n+2)(n+1)a_{n+2} (x - 1)^n + \sum_{n=0}^{\infty}a_n (x - 1)^n \\ & = \sum_{n=0}^{\infty}(x - 1)^n[n(n+1)a_{n+1} +(n+2)(n+1)a_{n+2} +a_n]\\ & = 0 \end{align}$

So it is 0 if and only if $n(n+1)a_{n+1} +(n+2)(n+1)a_{n+2} +a_n = 0 \iff a_{n+2} = -\dfrac{a_n}{(n+1)(n+2)} -\dfrac{na_n}{n+2}$

After solving I got this pattern

$a_2 = \dfrac{-a_0}{2}$

$a_3 = \dfrac{-a_1}{2\cdot 3}-\dfrac{a_2}{3}$

$a_4 = \dfrac{-a_2}{3\cdot 4}-\dfrac{2a_3}{4}$

For the initial conditions, is this correct?

$y(1) = \sum_{n=0}^{\infty}a_n (1 - 1)^n = a_0 = 5$ because all the other terms go to 0 and the limit of $0^0$ is 1

Same process

$y'(1) = y' = \sum_{n=1}^{\infty}na_n (1 - 1)^{n-1}= a_1 = 0$ because all the other terms go to 0 and the limit of $0^0$ is 1

If I am correct with I am doing so far then my solution should be $y \approx 5 - \frac{5}{2}x^2 + \frac{5}{6}x^3 - \frac{5}{24}x^4$

Thank you very much for taking the time to read

$\endgroup$
2
$\begingroup$

Your solution is correct. When the number of terms to determine is given in advance, I prefer not to write out the entire series at all. My quick-and-dirty solution would be

$$y=5+a(x-1)^2+b(x-1)^3+c(x-1)^4+O((x-1)^5)$$ $$y''=2a+6b(x-1)+12c(x-1)^2+O((x-1)^3)$$ $$xy''=y+(x-1)y''=2a+(2a+6b)(x-1)+(6b+12c)(x-1)^2+O((x-1)^3)$$ Hence $2a+5=0$, $2a+6b=0$, $a+6b+12c=0$, and the solution is $a=-5/2$, $b=5/6$, $c=-5/24$.

$\endgroup$
  • $\begingroup$ Oh that is cheap and dirty! $\endgroup$ – Hawk Jun 21 '12 at 23:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.